Is there a future for clinical ethics services in Australia? - Kerridge, I; Savulescu, J; Komesaroff, P (2001)
Clinical ethics refers to the consideration of ethical issues arising directly in the context of patient care. Health professionals are generally adept at effectively and sensitively managing ethical issues in clinical care. However, in some settings, multidisciplinary clinical ethics services may enhance clinical practice by assisting clinicians, patients and others to identify, understand and manage ethical issues. Clinical ethics services may be particularly valuable for situations in which moral perspectives diverge or communication has deteriorated. Such services may facilitate discussion and help the parties find mutually satisfactory solutions. Clinical ethics services may take various forms, including clinical ethics committees, ethics consultants, patient advocates or other mechanisms for responding to complaints and grievances. There is considerable disagreement about key aspects of clinical ethics services, including who should conduct them, how they should be run and what role they should play in decision-making.